Health Assets Project 2008 - Hensing, Gunnel; Holmgren, Kristina; Andersson, Lena; Krantz, Gunilla; Petersson, Eva-Lisa; Staland-Nyman, Carin (University of Gothenburg, 2013)
The Health Assets Project is being carried out by the GendiQ research group at the Unit of Social Medicine. The project examines the individual, organisational and societal factors affecting the return to work of people on sick leave, and what factors contribute to people not becoming sick-listed at all. The Health Assets Project is a longitudinal cohort study, with initially two data collection periods. The first was conducted in the spring of 2008 and the second was due in the autumn of 2009. The data was collected through mailed questionnaires and registry data. In the spring of 2008, a survey was mailed out to a sample drawn from the registers held by SCB and Social Insurance, comprising both sick and healthy people registered in the county.  The study population is based on three cohorts; the general population cohort, the sick-listed employer-reported cohort and the sick-listed self-reported cohort. In the first data collection in the spring of 2008, a total of 7 835 people participated, of which the population cohort comprised 4 027 people, the employer-reported cohort 3310 and the self-reported cohort 498. The proportion of women was higher then the men in all three cohorts, 55 % in the population cohort, 66 % in the employer-reported cohort and 65 % in the self-reported cohort.

Purpose:

The specific aims of the project are: 1) To examine the differences in self-reported health between a general population and incident sick-leave cohorts. 2) To examine the work-related factors that promote people returning to work after having been sick-listed. 3)To examine the living conditions, i.e. individual-related and psychosocial factors, that promote people returning to work after having been sick-listed. 4) To examine the factors that during the rehabilitation function as resources or barriers in the process from sick-leave to returning to work.

Dataset includes the 7835 individuals responding to the first questionnaire, in 2008.

Hälsoresursprojektet bedrivs av forskargruppen GendiQ vid enheten för socialmedicin, Göteborgs universitet. Projektet undersöker vilka individuella, organisatoriska och samhälleliga faktorer som påverkar att sjukskrivna personer återgår i arbete, och vilka faktorer som främjar att personer inte blir sjukskrivna överhuvudtaget. Hälsoresursprojektet är en longitudinell kohortstudie med initialt två datainsamlingsperioder. Den första genomfördes under våren 2008 och den andra under hösten 2009. Datainsamlingen sker genom enkätutskick och registerdata. Under våren 2008 gjordes ett enkätutskick till ett urval som var draget från SCB:s, respektive försäkringskassans register och innefattade både sjukskrivna och icke sjukskrivna personer som var folkbokförda i Västra Götalands län. Studiepopulationen består av totalt tre kohorter; en generell befolkningskohort och två sjukskrivningskohorter varav en arbetsgivaranmäld och en egenanmäld. I den första datainsamlingen under våren 2008 deltog 7 835 personer varav befolkningskohorten bestod av 4027 personer, den arbetsgivaranmälda kohorten av 3310 och den egenanmälda kohorten av 498. Andel kvinnor var högre än andel män i alla kohorter, 55 % i befolkningskohorten, 66 % i den arbetsgivaranmälda kohorten och 65 % i den egenanmälda kohorten.

Syfte:

Projektets specifika syften är att: 1) Undersöka skillnader i självrapporterad hälsa mellan en generell befolkning och incident sjukskrivningskohort. 2) Undersöka vilka arbetsrelaterade faktorer som främjar att människor återgår i arbete efter en sjukskrivning. 3) Undersöka vilka levnadsförhållanden, d v s individrelaterade och psykosociala faktorer, som främjar att människor återgår i arbete efter en sjukskrivning. 4) Undersöka vilka faktorer som under själva rehabiliteringen fungerar som resurser respektive hinder i processen från sjukskrivning till arbetsåtergång

Dataset innefattar de 7835 personer som under 2008 besvarade Hälsoresursprojektets första enkät.
Hälsoresursprojektet 2008
Keywords: CULTURE; KULTUR; LEISURE TIME; FRITID; CHILDREN; BARN; HOUSEWORK; HUSHÅLLSARBETE; JOB SATISFACTION; ARBETSTILLFREDSSTÄLLELSE; FAMILY LIFE; FAMILJELIV; FRIENDS; VÄNNER; DRINKING BEHAVIOUR; ALKOHOLVANOR; ILL HEALTH; OHÄLSA; DISEASES; SJUKDOMAR; SMOKING; RÖKNING; LABOUR AND EMPLOYMENT; ARBETE OCH SYSSELSÄTTNING; CIVIL STATUS; CIVILSTÅND; SEX; KÖN; LIFE EVENTS; LIVSHÄNDELSER; WORKPLACE; ARBETSPLATS; SICK LEAVE; SJUKFRÅNVARO; SYMPTOMS; SYMPTOM; REPETITIVE WORK; MONOTONT ARBETE; Longitudinal Studies; Longitudinella studier; Prospective Studies; Prospektiva studier; Exercise; Träning; Public Health; Folkhälsa; Health; Hälsa; Mental Health; Psykisk hälsa; Sick Leave; Sjukfrånvaro; Social Support; Socialt stöd; WORKING CONDITIONS; ARBETSFÖRHÅLLANDEN; LEISURE TIME ACTIVITIES; FRITIDSAKTIVITETER; PRIVATE HEALTH SERVICES; PRIVAT HÄLSOVÅRD; STATE HEALTH SERVICES; STATLIG HÄLSO- OCH SJUKVÅRD; HEALTH; HÄLSA; General health and well-being; Allmän hälsa och välbefinnande; Working conditions; Arbetsförhållanden; Family life and marriage; Familjeliv och äktenskap; Social welfare systems/structures; Sociala välfärdssystem/-strukturer; Cultural activities and participation; Kulturaktiviteter och deltagande; Medical and Health Sciences; Medicin och hälsovetenskap; Health Sciences; Hälsovetenskap; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin; Epidemiology; Epidemiologi